Faneuil Hall Square, ca. 1856 - Unknown (Tufts Archival Research Center, 2005)
Elevated view looking southeast from western end of Faneuil Hall toward South Market Street. The narrow opening to the left of the building with the Gun Store sign is Corn Court. A variety of business signage is affixed to many of the buildings in the area. Two horse-drawn vehicles are seen in the foreground of the image. Silas Peirce and Company Ltd letterhead is pasted to the back, on it is typed the building marked Gun Store was the store numbered 6 on the south side of the market where Silas Peirce was in business in 1816. 11 3/8 x 9 5/8 Photographs